2016
DOI: 10.1111/jcms.12398
|View full text |Cite
|
Sign up to set email alerts
|

A Feasible Unemployment‐Based Shock Absorber for the Euro Area

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…2 A harmonized unemployment insurance system within the Eurozone as a tool for international risk sharing has also been suggested by the President of the European Council (van Rompuy, 2012), the International Monetary Fund (Blanchard et al, 2014), the German Institute for Economic Research (Bernoth and Engler, 2013), the French Advisory Council (Artus et al, 2013), Dolls et al (2014), the Banca d'Italia (Brandolini et al, 2015) and Bénassy-Quéré et al (2016). Brenke (2013) also discusses some of the drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…2 A harmonized unemployment insurance system within the Eurozone as a tool for international risk sharing has also been suggested by the President of the European Council (van Rompuy, 2012), the International Monetary Fund (Blanchard et al, 2014), the German Institute for Economic Research (Bernoth and Engler, 2013), the French Advisory Council (Artus et al, 2013), Dolls et al (2014), the Banca d'Italia (Brandolini et al, 2015) and Bénassy-Quéré et al (2016). Brenke (2013) also discusses some of the drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that such a scheme would need to be implemented in stages. In November 2014, the Bank of Italy published a paper identifying the broad characteristics that a shock absorber based on unemployment should have in order to be incentive-compatible and politically feasible (Brandolini et al 2014). The study derives empirically the combination of activation thresholds, experience rating, eligibility criteria and benefit generosity to define such a system giving rise to macro-cross-national transfers, activated by a trigger and with partial experience rating.…”
Section: Recent Proposalsmentioning
confidence: 99%
“…Fourth, studies have proved that even systems that do not redistribute resources between countries can have an important stabilisation impact in the medium run (Brandolini et al 2014). …”
Section: How To Design a European Unemployment Insurance Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Claeys et al (2014) provide an overview of policy challenges associated with an EMU-UI system. 4 Brandolini et al (2016) and Jara and Sutherland (2014) also use micro data to analyze an EMU-UI system. The focus of their analyses di¤ers from ours as in contrast to this study, the former considers a notional EMU-UI system backing national UI systems and thus disregards EMU-UI transfers at the micro level, while the latter assumes EMU-UI bene…ts to top up national bene…ts if minimum requirements are not met by national UI systems.…”
Section: Introductionmentioning
confidence: 99%